2011
DOI: 10.1007/s11856-011-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

An ordinal indexing on the space of strictly singular operators

Abstract: Using the notion of S ξ -strictly singular operators introduced by Androulakis, Dodos, Sirotkin and Troitsky, we define an ordinal index on the subspace of strictly singular operators between two separable Banach spaces. In our main result, we provide a sufficient condition implying that this index is bounded by ω 1 . In particular, we apply this result to study operators on totally incomparable spaces, hereditarily indecomposable spaces and spaces with few operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Denote the subclass of S ξ -strictly singular operators by S ξ -S. It is clear that S 0 -S coincides with the class of compact operators. These classes where defined in [3] and have been extensively studied [2,11,14,48]. In particular, while it is shown that (S ξ -S) ξ<ω 1 separably refines S. In general, S ξ -S need not satisfy the additive property of being an operator ideal [45].…”
Section: Weakly Compact Operators and Subclasses An Operatormentioning
confidence: 99%
“…Denote the subclass of S ξ -strictly singular operators by S ξ -S. It is clear that S 0 -S coincides with the class of compact operators. These classes where defined in [3] and have been extensively studied [2,11,14,48]. In particular, while it is shown that (S ξ -S) ξ<ω 1 separably refines S. In general, S ξ -S need not satisfy the additive property of being an operator ideal [45].…”
Section: Weakly Compact Operators and Subclasses An Operatormentioning
confidence: 99%
“…In this paper when we refer to a Borel subset of L(X, Y ) it is understood that this is with respect to the Borel σ-algebra generated by the strong operator topology. There are several papers in which L(X, Y ) is considered with this structure [4,5,6].…”
Section: Preliminariesmentioning
confidence: 99%
“…In [1] they prove that each weakly compact operator on X is strictly singular. It is shown in [4] that when the strictly singular operators have codimension-one in L(X) they are a Borel subset. It follows that the set of weakly compact operators on X is a Borel subset of L(X).…”
Section: Applicationsmentioning
confidence: 99%
“…In particular, the map T → ̺(T ) is an ordinal rank 1 on the set SS(X, Y ) of all strictly singular operators from X to Y . It was further studied in [3,8,11,23].…”
Section: Introductionmentioning
confidence: 99%